ANALISIS SENTIMEN TWITTER TERHADAP NYAMUK WOLBACHIA MENGGUNAKAN METODE LSTM DENGAN PENDEKATAN NLTK - Lakoro, Tiara; K. Nasib, Salmun; Imansyah Yahya, Nisky; S. Panigoro, Hasan; Nurmardia Abdussamad, Siti (Cahaya Ilmu Bangsa Institute, 2025)
Dengue Hemorrhagic Fever (DHF) is one of the major health issues in Indonesia. One of the preventive measures is the Wolbachia mosquito program. However, the implementation of this program has sparked various reactions from the public, which can be observed through social media, particularly Twitter. This study aims to analyze public sentiment towards Wolbachia mosquitoes using the Long Short-Term Memory (LSTM) method and the Natural Language Toolkit (NLTK) approach. Data was collected through a crawling process from Twitter using keywords related to